Spatial Diversification of the Balance on the Labour Market in Rural areas in Poland - Stanny, Monika (Bulletin of Geography. Socio-economic Series, 2010)
The purpose of the study is to present the spatial diversification of the level of the balance on the local labour market in the rural areas. The spatial unit of the analysis is constituted by rural communes (gminas) and the rural areas of the urban-rural communes in Poland according to the administrative division into town and village. This means that the research concerns the spatial diversification observed according to 2,171 units. It was accepted in the research that a balanced labour market occurs where favourable demographic structures are located around the largest regional centres in Poland. This is connected with the development of the communes' non-agricultural economic functions and a strong dependence on urban markets.